Feeding children: meanings from the voice of mothers in the light of Symbolic Interactionism - Lizalde Hernández, Azucena (2023)
The objective of this essay was to reflect on the meanings about eating habits from the mothers' voice through Symbolic Interactionism. Food is a basic need for people and provides the body with the nutrients it needs for optimal functioning and health preservation. Unhealthy diets are among the top ten risk factors for disease worldwide, behaviors characterized by consumption of sugary drinks, carbohydrates and high salt content. It is a problem in which social and cultural factors are involved in each context or region; mothers as social beings attribute meanings to food, select, prepare, consume and give food to their children; understanding the meaning as a social product that motivates unhealthy eating behavior derived from the interaction in the upbringing of their children, family and society. Meaning constitutes the surface through which the possibility of understanding is raised which is the basis of humanism itself and understanding needs to be contextualized in the real world of people, exercising the ability to place oneself in the place of the other through an inductive process, generating scientific knowledge derived from a sensory experience, facts felt, seen and heard.